دراسة موسمية لكمية ونوعية الهائمات النباتية في المصب العام _ القادسية _ العراق - علكم, فؤاد منحر (University of Thi-Qar Journal of Science, 2013)
The present study was conducted during the period of November 2011 to October 2012. Three  stations were fixed to achieve the study. This study phytoplankton in the main outfall drain in Qadisiyah  province.The study involved measuring some physical and chemical properties to Main Outfall Drain water which included water temperature, light penetration, PH, dissolved oxygen and total hardness. The number of species of phytoplankton taxa 205 species belonging to 66 genus as as Bacillariophycaea were theprevailing rate of 70.24%, and the rate of (144) species, followed by Chlorophytceae that recorded (31) species by 15.12% , Cyanophyceae by 11.7% (24) species and then Euglenaphceae 1.46 % (3) type then followed by Pyrrophceae, the 1.46% (3) type. As for the density of phytoplankton were Daytomats and record types as (Cyclotella meneghiniana) the highest density of species and more impressions for the duration of the study in all the stations studied, also marked the third stations the highest density Quarterlyas for the observed changes monthly and locally during the study period.